Modernity vs Traditionality: The Approach the Vernacular Architecture in Maintaining Traditional Architecture through Structuralism - Tarigan, Riandy (CV. Gio Architect, 2023)
The development of current functions in traditional homes is similar to the development of homes in general. The function of the house is not only as a place of residence for residents, but as another function. Residents develop additional functions, such as business functions or cultural functions. The addition of this function has an impact on the reduction or loss of the meaning of traditional architecture due to changes in activities and ways of view of the inhabitants of their traditional spaces. The purpose of the discussion was to find out the dynamics of the meaning of modernity and traditionality in space and the traditional forms of traditional houses. The approach is carried out through Semiotics and Structuralism which is reading the dynamics of the relationship between the meaning of traditionality and modernity through architectural signs in traditional houses. The method of discussion is descriptive-interpretive method that is to look at cultural phenomena that are behind the dynamics of traditional functions, spaces and forms by showing the developmental relations of functions to the dynamics of the meaning of space and form. The results of this paper are expected to provide a theoretical contribution to the development of traditional house and space and contribute to the right method in the process of changing space and form without leaving its traditional values, so that traditional houses can keep abreast of the times.